AREA-EFFECT IN BREEDING BIRD COMMUNITIES OCCURRING IN AN ARCHIPELAGO OF URBAN HOLM OAK FRAGMENTS (ROME, CENTRAL ITALY) - Arca, E.; Battisti, C.; Fraticelli, F. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 2012)
We carried out a study on breeding bird communities occurring in anarchipelago of 32 holm oak fragments in an urbanized landscape (Rome, central Italy). The log-transformed species-area relationship is comparable with other ``insular{''} situations obtained from analogous mainland fragmented landscapes. We observed a quick decrease of species number when area size is lower than 2 hectares, with a significant threshold at 1 ha, unlike rural areas in which a quick species decrement occurs on a higher area size range (< 10 hectares). Species appear differently sensitive to area size of the fragments with significant responses in Dendrocopos major, Aegithalos caudatus, Sitta europaea, Parus major, Certhia brachydactyla and Fringilla coelebs. Considering the recreational role of the biodiversity for human populations inhabiting large metropolitan areas, the threshold in size (about 1 ha in fragment area) evidenced in this study may be useful for urban park management strategies.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: SPECIES-AREA RELATIONSHIP; AREA-SENSITIVE SPECIES